IMPACT OF ISLAMIC FINANCIAL LITERACY ON FINANCIAL RETIREMENT PLANNING INTENTION AMONGST INDONESIAN MUSLIM STUDENT IN A MALAYSIAN UNIVERSITY - Kurnia, Zahra Nabila; Syed Musa, Alhabshi; Redzuan, Nur Harena (IIUM Institute of Islamic Banking and Finance, 2021)
A longer investment horizon period will benefit the youth in actualizing their financial wellbeing in their post-employment period. It is important to identify the younger generation's intentions, who are represented by university students, regarding their financial retirement planning in the near future. Besides, an expected longer employment life span of young Muslims should be equipped with an adequate level of Islamic financial literacy to create accurate Shariah-compliant financial decisions, including their retirement interests. Therefore, this study aims to measure the Islamic Financial Literacy (IFL) among Indonesian Muslim students in International Islamic University Malaysia (IIUM). The study also examines the impact of IFL and several demographic factors which are gender, age, marital status, and education level toward the intention of having voluntary Shariah retirement savings. The data were collected from 150 undergraduate and postgraduate students. Using the ordinal logistic regression method, the results of the study reveal that IFL positively affects the intention of having voluntary Shariah retirement savings. The impact of the demographic factors on the intention has been found as insignificant. Correspondingly, this study will assist the policymakers, industry players, and financial educators in developing policies related to Shariah retirement savings products, making commercial decisions, and developing strategies to enhance people's awareness of Islamic retirement planning. Furthermore, it will enrich the academic literature and for further research, specifically concerning Islamic retirement planning among youth, which lacks empirical studies.